Inequalities in early childhood and families - Erola, Jani; Heiskala, Laura; Karonen, Esa; Kilpi-Jakonen, Elina (My University, 2026)
The early childhood family contexts are considered formative for adult educational and socioeconomic outcomes. We study the intergenerational impacts of parental education and economic resources, as well as family structure, and consider the modifying effects of local educational opportunity structures on social and genetic influences on educational and socioeconomic attainment.